Intervenors intervened: organizational predicaments and institutional contradictions in the production of export plantains in the Atlantic Zone of Costa Rica: Field Report - Atlantic Zone Programme (CATIE-AUW-MAG) no. 88 - Veerchoor, G. (1992)
45 páginas